Effect of Grinding and Resintering on the Fatigue Limit and Surface Characterization of a Y-TZP Ceramic - Polli,Gabriela Scatimburgo (2016)
Abstract This study evaluated the effect of grinding protocols and resintering on flexural fatigue limit and surface characterization of LavaTM Y-TZP. Bar-shaped specimens (20×4.0×1.2 mm, n=40; 20×4.0×1.5 mm, n=80) were obtained. Half of the thinner specimens (1.2 mm) constituted the as-sintered group (AS), while the thicker ones (1.5 mm) were ground with diamond burs under irrigation (WG) or not (G). The other half of thinner and half of ground specimens were resintered (1000 ºC, 30 min), forming the groups ASR, WGR and GR. Fatigue limit (500,000 cycles, 10 Hz) was evaluated by staircase method in a 4-point flexural fixture. Data were analyzed by 2-way ANOVA and Tukey's test (α=0.05). Surface topography (n=3) and fracture area (n=3) were evaluated by SEM. X-ray diffraction data (n=1) was analyzed by Rietveld refinement. ANOVA revealed significant differences (p<0.001) for the grinding protocol, resintering and their interaction. Grinding increased the fatigue limit of non-resintered groups. There was no significant difference among the resintered groups. Resintering significantly increased the fatigue limit of the AS group only. Both protocols created evident grooves on zirconia surface. The failures initiated at the tensile side of all specimens. The percentages (wt%) of monoclinic phase were AS (8.6), ASR (1.2), G (1.8), GR (0.0), WG (8.2), WGR (0.0) before, and AS (7.4), ASR (6.5), G (3.2), GR (0.2), WG (4.6), WGR (1.1) after cyclic loading. Grinding increased the fatigue limit of non-resintered Y-TZP and formed evident grooves on its surface. Resintering provided significant increase in the fatigue limit of as-sintered specimens. In general, grinding and resintering decreased or zeroed the monoclinic phase.